Model Perlindungan Hukum terhadap Hak Tenaga Kerja Wanita dalam Kontrak Kerja Perkebunan Sawit Aceh Utara - Eko Gani PG; Muksalmina Muksalmina; Tasyukur Tasyukur; Nabhani Yustisi; Eka Chyntia (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
This study aims to analyze the legal protection of women workers in employment contracts within the palm oil plantation sector in North Aceh Regency, with particular emphasis on the gap between normative regulations and their implementation in practice. The research employed a normative-empirical legal approach by combining statutory analysis with field data collected through interviews and observations with women workers, company representatives, and local labor authorities. The analysis was conducted qualitatively to compare the provisions of labor laws regarding maternity leave, menstrual leave, reproductive health rights, and social security with actual conditions experienced by women workers, most of whom are employed under daily or short-term contracts. The findings show that written contracts often fail to guarantee fundamental rights, while weak government oversight and persistent gender discrimination exacerbate the precarious position of women workers. The study concludes that an integrative model of legal protection is needed, which combines clear and fair contractual arrangements, effective state supervision, active participation of labor unions, and continuous gender-based legal education. Such a model is expected to ensure more equitable and humane working conditions for women workers in the palm oil plantation sector